School Management System: Human Resource Management System Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Human Resource Management System (HRMS) is a system that may structure andcomprehensively simplify multiple human resource tasks, empowering individuals to improvetheir knowledge and abilities for career growth. These will provide a simpler method formoving the organization and its people toward goals while avoiding risk. This project studyattempted to eliminate the harm caused to any developing organization by poorly managedemployee evaluation, a lack of career pathing, and employee information vulnerability. Toaddress the concerns and problems identified in this project study, the project team created aHuman Resource Management System at Bestlink College of the Philippines.As a result, it solves the issues and difficulties that human resource management faces. Thisresults in a more efficient method of assessing employee competency, a discernibleimprovement in employee retention, a secured career path because of the implementation ofSuccession Planning, a more central role for learning and development programs in everybusiness, and finally, a Multipurpose Employee’s Profile that is flexible enough to be accessedfrom mobile and desktop.This project will improve the operation and functionality of the Human Resources Department.The integration of the system in this project will make all of the reports required to assess eachemployee, including selecting applicants for the specific position, accessible to efficientlyanalyze employee competency, learning, and training development. Furthermore, acentralized employee profile allows each individual to check personal details such asschedules, pay stubs, and more, including announcements, from a computer or mobilebrowser.
Keywords: IT & Management